Secondary growth of ZIF-8 films onto copper-based foils. Insight into the surface interactions - Papporello, Rocío L. (2015)
The film growth of the zeolitic imidazolate framework-8 on a copper-based substrate is reported for the first time in the literature. The growth mechanism on copper foils is analyzed, and it is demonstrated that during synthesis the development of the metal-organic framework (MOF) film is sensitive to the interactions produced between the support surface, the solvent and the reactants. In order to compare the surface interactions during synthesis, Fecralloy foils, porous alumina disks and macroporous cordierite monoliths are also analyzed. The physicochemical properties of the materials are evaluated by XRD, SEM, EPMA, AAS, DRIFT and XPS. In DMF-based media, no ZIF-8 film develops on the copper surface due to unfavorable interactions that make its growth non selective. At the same time, the formation of a dense ZnO layer is favored, this layer being promoted by decomposition products of the solvent and the zinc reagent. When water-based media are used, those interactions are modified thus avoiding the formation of oxide, but the growth kinetics of the ZIF-8 film is still low. On the other hand, when using mixtures based on methanol with the addition of acetate, continuous, uniform, and adherent ZIF-8 films can be obtained. Such films develop preferential crystallographic orientations in planes {200} and {110}, have thicknesses between 5 to 10 microns and good mechanical and thermal stability. The results obtained provide a platform for the obtention of ZIF-8 films on copper structures, which is relevant for the development of new structured catalysts based on MOFs.